Butterfly Hug Therapy in Reducing Students' Anxiety in Facing Final Assignment Exams - Nurmaya Sari; Neiliel Fitriana Anies; Afni Yan Syah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Anxiety is a psychological problem often experienced by students, especially when facing final exams. Anxiety that is not handled properly can interfere with academic performance and mental health. One non-pharmacological approach that can be used to overcome anxiety is butterfly hug therapy. Butterfly hug therapy is a simple bilateral stimulation technique that can be done independently to help reduce anxiety. This study aims to determine the effectiveness of butterfly hug therapy in reducing student anxiety. this study used a quasi experiment with one grup pretest-posttest design. Sampling in this study used purposive sampling with the following criteria: willingness to be a respondent, being a sixth-semester final-year student who had not yet taken their final exams, and having mild to moderate anxiety score as screened using the Hamilton Anxiety Rating Scale (HARS). The sample obtained after screening consisted of 22 students experiencing mild to moderate anxiety. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after six intervention sessions. HARS has a Cronbach's Alpha reliability coefficient of 0.86, indicating an excellent level of internal consistency. In addition, content validity testing has been conducted by nursing and psychology experts, showing that each item is relevant for measuring the dimension of anxiety. The paired t-test analysis showed that butterfly hug therapy was proven to be significantly effective in reducing anxiety (p 0.000 (<0.05)). butterfly hug therapy can be used as a practical and effective non-pharmacological intervention in managing student anxiety and can be integrated into mental health promotion in higher education institutions.